PENGARUH LITERASI KEUANGAN DAN LINGKUNGAN KAMPUS TERHADAP MINAT BERINVESTASI MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Fealty, Patrisia Maria; Okianna, Okianna; Budiman, Jumardi; Syahrudin, Husni; Syamsuri, Syamsuri (STKIP Persada Khatulistiwa Sintang, 2023)
The tendency for someone to have the intention to invest means that person will take action to achieve their desire to invest. Understanding financial literacy and a good campus environment can be a factor in wanting to invest so that you can generate financial results in the future. This research aims to find out how much influence financial literacy and the campus environment have on investment interest for FKIP UNTAN Economics education students. The research method used in this research is multiple linear with quantitative form. The source of research data is students of the economics education study program FKIP UNTAN, namely the Class of 2019 and 2020, Regular A and PPAPK classes and the data was obtained through a questionnaire from Google Form. The sample used was 78 students. Classic hypothesis testing includes normality, multicollinearity, and heteroscedasticity. The tests used include the F test, t test, and R2 test. The research results concluded that Financial Literacy has a significant influence on interest in investing. The campus environment has a significant influence on investment interest. Financial literacy and the campus environment simultaneously influence students' investment interest